Analisis Efisiensi Pengelolaan Sampah di TPA Losari, Wonorejo, Selomerto, Wonosobo - Wirdati, Alvina Chusnul; Anggraini, Dian (Lembaga Yasin AlSys, 2023)
This research aims to analyze the efficiency of waste management at the Final Disposal Site (TPA) Losari, Wonorejo, Selomerto, Wonosobo. TPA Losari is a strategic location for waste management in the Wonosobo region and is under the supervision of the Environmental and Forestry Agency of the district. The study was conducted through direct observation of the waste collection, sorting, and management processes at the TPA. The results indicate that the monitoring and coordination by the Environmental and Forestry Agency focus on responsible and sustainable waste management at TPA Losari. Organic waste is processed through sorting and natural decomposition, while inorganic waste is sorted by waste pickers to support recycling efforts. There is also specific management for medical waste, requiring careful handling. However, TPA Losari is currently facing a